Réponses

2014-05-15T18:21:57+02:00
A = 3a + 5 - (2a + 7) + (8 - 5a)
A = 3a + 5 - 2a - 7 + 8 - 5a
A = 3a - 2a - 5a + 5 - 7 + 8
A = - 4a + 6

B = b + 4 + ((3b - 2) - (8b - 5)
B = b + 4 + 3b - 2 - 8b + 5
B = b + 3b - 8b + 4 - 2 + 5
B = - 4b + 7

C = 6 - 5c + 3c - (4 - 6c) + 5 + (7 - 2c)
C = 6 - 5c + 3c - 4 + 6c + 5 + 7 - 2c
C = - 5c + 3c + 6c - 2c + 6 - 4 + 5 + 7
C = - 7c + 9c + 18 - 4
C = 2c + 14

D = d - 1 - (3d + 4) + (5 - 4d) - (7d + 5) + 5
D = d - 1 - 3d - 4 + 5 - 4d - 7d - 5 + 5
D = d - 3d - 4d - 7d - 1 - 4 + 5 - 5 + 5
D = - 13d